100x-29=100(426.71)

Simple and best practice solution for 100x-29=100(426.71) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 100x-29=100(426.71) equation:


Simplifying
100x + -29 = 100(426.71)

Reorder the terms:
-29 + 100x = 100(426.71)

Multiply 100 * 426.71
-29 + 100x = 42671

Solving
-29 + 100x = 42671

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + 100x = 42671 + 29

Combine like terms: -29 + 29 = 0
0 + 100x = 42671 + 29
100x = 42671 + 29

Combine like terms: 42671 + 29 = 42700
100x = 42700

Divide each side by '100'.
x = 427

Simplifying
x = 427

See similar equations:

| -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a | | 17(3)= | | 7p=50.4 | | 8x+14=12x-22 | | 3(x+5)+4(x-3)-6x=4 | | 17m=170 | | (x)(x+8)=96 | | 120-4x=40 | | 12-5x=-58 | | 7+9x=97 | | A(6a-3)= | | 2+8x=66 | | 6/2X+14 | | 11-4*x+1-3=11+2*4-2x-16 | | 7x-2=103 | | 3.5(c-8)+c=125 | | 6/(2X)=14 | | 9=6x-15 |

Equations solver categories